2014
DOI: 10.1007/s10336-014-1096-y
|View full text |Cite
|
Sign up to set email alerts
|

High glucose concentrations are associated with symptoms of mild anaemia in Whiskered Terns: consequences for assessing physiological quality in birds

Abstract: Although blood concentrations of glucose and haemoglobin are known to correlate with nutritional state of individuals, hyperglycaemic states in vertebrates are often linked to anaemia. A negative relationship between blood concentrations of glucose and haemoglobin was confirmed in a wild population of Whiskered Terns Chlidonias hybrida. Also, terns with higher haemoglobin concentrations initiated laying earlier and had clutches with larger eggs, while blood glucose concentrations of individuals were not associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…Therefore, a negative correlation between the concentration of haemoglobin and glucose would be expected, as recently reported by Minias (2014).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, a negative correlation between the concentration of haemoglobin and glucose would be expected, as recently reported by Minias (2014).…”
Section: Introductionmentioning
confidence: 61%
“…Our previous findings on tits foresaw the possibility of such a relationship (Bańbura et al 2007;Kaliński et al 2014), and it would be expected, assuming that hyperglycaemic states are likely to co-occur with anaemic symptoms in vertebrates. Minias (2014) found a strong negative correlation between the concentrations of haemoglobin and glucose in adult Whiskered Tern Chlidonias hybrida. This author stated that he was not aware of any other studies with empirically evaluated associations between blood concentrations of haemoglobin and glucose in wild populations of birds, and that more empirical studies were necessary to determine whether it could be considered as a general pattern in wild-living avian species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, predators may choose to forage selectively in the parts of the colony occupied by individuals of lower quality (e.g. There is also evidence from other waterbird species that individuals with higher blood haemoglobin concentrations were more likely to breed and started breeding earlier in the season (Crossin et al 2013), as well laying larger eggs (Minias 2014b). Although we lacked empirical data on the age of gulls nesting in our colony, it seems probable that older individuals might be more likely to settle in the central part of the colony, as similar patterns have already been reported for other colonial waterbirds, including larids (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Haemoglobin concentration is considered a robust proxy of physiological condition in birds and has been reported to correlate, among other parameters, with fat reserves, diet quality and developmental stability (reviewed in Minias 2015). There is also evidence from other waterbird species that individuals with higher blood haemoglobin concentrations were more likely to breed and started breeding earlier in the season (Crossin et al 2013), as well laying larger eggs (Minias 2014b). Thus, we concluded that higher haemoglobin concentrations of centrally nesting Black-headed Gulls were a good indicator of their enhanced physiological condition after clutch completion.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects the presence of pathogens and parasites, as well as the nutritional status of organism (a drop in haemoglobin concentration suggests nutritional deficiency ;Campbell 1995;Simon et al 2004;Kasprzyk et al 2006;Słomczyński et al 2006). All those features support the use of the haemoglobin level as a relatively reliable indicator of physiological condition in field and experimental studies on birds (Stevens 1996;Kilgas et al 2006a;Kaliński et al 2009Kaliński et al , 2012Pyrke and Rollins 2012;Lill et al 2013;Minias 2014;Minias et al 2014;Glądalski et al 2015a). But it is important to emphasize that some recent studies recommend caution when using blood characteristics to evaluate physiological condition in some species (Fair et al 2007;Lill et al 2013;Minias 2015;Johnstone et al 2015).…”
Section: Introductionmentioning
confidence: 99%